2017
DOI: 10.1002/adom.201700982
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐Wave Lasing in Cesium Lead Bromide Perovskite Nanowires

Abstract: mixing or exchange of cations or anions, covering the complete visible and near-IR wavelength region; (iii) they show lasing at carrier densities as low as 10 16 cm −3 , which is two orders of magnitude lower than those in conventional semiconductor NWs. [9] However, all lead halide perovskite NW lasers demonstrated thus far are limited to pulsed operation. While continuous wave (CW) lasing is vital to achieving electrically injected NW lasers and to applications such as optical communication and spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
218
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(227 citation statements)
references
References 49 publications
4
218
3
1
Order By: Relevance
“…The end facets of the nanowire will reflect part of the light back, forming the laser cavity with optical modes spaced inversely proportional to the length of the nanowire. With sufficient optical pumping both single and multimode lasing are possible inside the nanowire . Inside a nanoplatelet, light can be trapped in whispering gallery modes, where photons circulate in a closed loop inside the platelet due to total internal reflection at the edges.…”
Section: Applicationsmentioning
confidence: 99%
“…The end facets of the nanowire will reflect part of the light back, forming the laser cavity with optical modes spaced inversely proportional to the length of the nanowire. With sufficient optical pumping both single and multimode lasing are possible inside the nanowire . Inside a nanoplatelet, light can be trapped in whispering gallery modes, where photons circulate in a closed loop inside the platelet due to total internal reflection at the edges.…”
Section: Applicationsmentioning
confidence: 99%
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [6][7][8][9][10] In addition to light absorption or conversion for energy capture, these materials have been reported for possible use in laser media, [11][12][13][14] LEDs, [15][16][17][18] and photodetectors. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…The room-temperature Rabi splitting energy determined by coupling strength in these NWs were ~210 ± 13, 146 ± 9 and 103 ± 5 meV for the CsPbCl 3 , CsPbBr 3 , and CsPbI 3 NWs, respectively. Zhu et al further realized the CW lasing in CsPbBr 3 NWs with a threshold of ~6 kW/cm 2 ( Figure 3F) [57]. A vacuum Rabi splitting of 0.20 ± 0.03 eV was achieved from the polariton modes near the bottleneck region on the lower polariton branch.…”
Section: Perovskite F-p Lasersmentioning
confidence: 93%